The shrunk genetic diversity of coral populations in North-Central Patagonia calls for management and conservation plans for marine resources - Anna Maria Addamo; Serena Zaccara; Vreni Häussermann; Juan Höfer; Günter Försterra; Ricardo García-Jiménez; Giuseppe Crosa; Annie Machordom (Scientific Reports, 2022)
Abstract The Chilean Patagonia is a complex puzzle of numerous fjords, channels, bays, estuaries, and islands. The largest part of it is very remote, hampering the generation of scientific knowledge and effective management planning that could balance conservation of the marine resources with the increasing development of aquaculture activities. The present study focuses on the deep-water emergent cold-water coral Desmophyllum dianthus, dwelling in Chilean Patagonia, with the aim to illustrate its population genetic structure, demography and adaptation of the species along this coast. Microsatellite loci analysis included D. dianthus individuals from twelve sampling localities along bathymetric and oceanographic gradients from the latitude 40°S to 48°S. The results showed a lack of genetic structure with an asymmetric dispersion of individuals, and relevant heterozygosity deficiency in some populations. This study also analyses the natural and human impacts affecting the region (e.g., climate change, increasing salmon farming activities), and stresses the importance of including genetic information in the process of management and conservation of marine resources. In particular, the relevance of using interdisciplinary approaches to fill the gaps in scientific knowledge especially in remote and pristine areas of western Patagonia. Therefore, information on genetic spatial distribution of marine fauna could become pivotal to develop a holistic ecosystem-based approach for marine spatial planning.